Lipid Droplets in Unicellular Photosynthetic Stramenopiles - Guéguen, Nolwenn; Le Moigne, Damien; Amato, Alberto; Salvaing, Juliette; Maréchal, Eric (Frontiers in Plant Science, 2021)
The Heterokonta or Stramenopile phylum comprises clades of unicellular photosynthetic species, which are promising for a broad range of biotechnological applications, based on their capacity to capture atmospheric CO2 via photosynthesis and produce biomolecules of interest. These molecules include triacylglycerol (TAG) loaded inside specific cytosolic bodies, called the lipid droplets (LDs). Understanding TAG production and LD biogenesis and function in photosynthetic stramenopiles is therefore essential, and is mostly based on the study of a few emerging models, such as the pennate diatom Phaeodactylum tricornutum and eustigmatophytes, such as Nannochloropsis and Microchloropsis species. The biogenesis of cytosolic LD usually occurs at the level of the endoplasmic reticulum. However, stramenopile cells contain a complex plastid deriving from a secondary endosymbiosis, limited by four membranes, the outermost one being connected to the endomembrane system. Recent cell imaging and proteomic studies suggest that at least some cytosolic LDs might be associated to the surface of the complex plastid, via still uncharacterized contact sites. TAG molecules contain acyl groups, whose carbon-length and number of double bonds depend on their origin. De novo synthesis produces long chain saturated or monounsaturated fatty acids (SFA, MUFA), whereas subsequent maturation processes lead to very-long-chain polyunsaturated FA (VLC-PUFA). TAG composition in SFA, MUFA and VLC-PUFA reflects therefore the metabolic context that gave rise to the formation of the LD, either via an early partitioning of carbon following FA de novo synthesis and/or a recycling of FA from membrane lipids, e.g. plastid galactolipids or endomembrane phospho- or betaine lipids. In this review we address the relationship between cytosolic LDs and the complex membrane compartmentalization within stramenopile cells, the metabolic routes leading to TAG accumulation, and the physiological conditions that trigger LD production, in response to various environmental factors.